2019
DOI: 10.1155/2019/7638946
|View full text |Cite
|
Sign up to set email alerts
|

RYR1Sequence Variants in Myopathies: Expression and Functional Studies in Two Families

Abstract: The skeletal muscle ryanodine receptor (RyR1), i.e., the Ca2+ channel of the sarco/endoplasmic reticulum (S/ER), and the voltage-dependent calcium channel Cav1.1 are the principal channels involved in excitation-contraction coupling in skeletal muscle. RYR1 gene variants are linked to distinct skeletal muscle disorders, including malignant hyperthermia susceptibility and central core disease (CCD), mainly with autosomal dominant inheritance, and autosomal recessive myopathies with a broad phenotypic and histop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…In our research, we found that MYH11 has mutations in 7 patients, and we found two pathogenic or possibly pathogenic mutations (rs375159635, rs751495086), which may be related to the pathogenesis of Hypopharyngeal carcinoma. In addition, SDHA is mainly related to gangliomas [28-30], RYR1 is mainly related to myopathy [31,32], and TTN is mainly related to dilated cardiomyopathy [33,34]. Interestingly, we found that these three genes have mutations in more than ve patients, and all of them have two or more pathogenic or possibly pathogenic mutation sites, which indicates their potential in the pathogenesis of Hypopharyngeal carcinoma.…”
Section: Discussionmentioning
confidence: 82%
“…In our research, we found that MYH11 has mutations in 7 patients, and we found two pathogenic or possibly pathogenic mutations (rs375159635, rs751495086), which may be related to the pathogenesis of Hypopharyngeal carcinoma. In addition, SDHA is mainly related to gangliomas [28-30], RYR1 is mainly related to myopathy [31,32], and TTN is mainly related to dilated cardiomyopathy [33,34]. Interestingly, we found that these three genes have mutations in more than ve patients, and all of them have two or more pathogenic or possibly pathogenic mutation sites, which indicates their potential in the pathogenesis of Hypopharyngeal carcinoma.…”
Section: Discussionmentioning
confidence: 82%
“…In our research, we found that MYH11 mutated in 7 patients, and we found two pathogenic or possibly pathogenic mutations (rs375159635, rs751495086), which may be related to the pathogenesis of hypopharyngeal cancer. In addition, SDHA is mainly related to gangliomas 30 32 , RYR1 is mainly related to myopathy 33 , 34 , and TTN is mainly related to dilated cardiomyopathy 35 , 36 . Interestingly, we found that these three genes have mutations in more than five patients, and all of them have two or more pathogenic or possibly pathogenic mutation sites, which indicates their potential in the pathogenesis of hypopharyngeal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…As previously described, HEK-293 cells transfected with RYR1 /pBI (wild-type) or one of the three RYR1 /pBI mutants (p.Thr84Met [ 14 ], p.Ser2345Arg [ 15 ], or p.Ala4894Thr [ 16 ]) were washed with Hank's balanced salt solution (HBSS) containing 130 mM sodium chloride (NaCl), 5.4 mM potassium chloride (KCl), 20 mM HEPES, 2.5 mM calcium chloride (CaCl 2 ), 1 mM magnesium chloride (MgCl 2 ), and 5.5 mM glucose (pH 7.4). The cells were loaded with 5.0 μ M Fura-2 AM (Dojindo Molecular Technologies, Tokyo, Japan) in HBSS for 1 hour at 37°C and then washed with HBSS.…”
Section: Methodsmentioning
confidence: 99%